Hot melt extrusion: a state of the art and multifunctional technique for oral film formulation - Taheya, Rezwana Tabassum (Brac University, 2020)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Pharmacy, 2019.